Climate change awareness and information utilisation and dissemination in rural areas of Nsanje District - Bizeck, Francis (Social, Ecology, Economy for Sustainable Development Goals Journal, 2024)
Background: Climate information communication is the heart of climate service delivery which provide knowledge to help guide individuals and other stakeholders to make climate smart decisions. Therefore, this study explored awareness, utilization and dissemination of climate information in rural areas of Nsanje district. Methods: The study used both quantitative and qualitative research design that does not involve the designing of an experiment. This focuses much on the descriptive research design. The advantage of using this research design in this study was that the participants’ accuracy was clearly depicted. Findings: The results showed that 63% of the people in rural areas access climate information through radio and 33% do not use it at all. Multinomial logistic regression indicate that floods and crop pests are significant predictors of the location of an individual whether lives in flood prone area or not with p-values of 0.02 and 0.04 respectively, and this shows that people understand climate change based on the impacts felt. This also shows that crop pests are more prevalent in flood prone zones. Conclusion: The study concluded that there is a need to adopt climate communication channels that are more interactive and recruit more extension workers who are agents to promote the use of climate information. Novelty/Originality of this article: This study proposes developing a community-based interactive climate communication model that integrates mobile technology and local extension worker networks to improve the accessibility and understanding of climate information in rural areas.